Preoperative Routine Cold-water Immersion for Lipedema Reduction Surgery - Jaime S. Schwartz, MD; Eva Danesh, BA; Noah Danesh, MPH; Arash Raghebi, BS; Jonah Danesh; Justin West, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Routine cold-water immersion (CWI) is typically suggested to reduce inflammation, a hallmark property of lipedema. Lipedema is a connective tissue disorder with a genetic component that presents with a disproportionate distribution of nodules in the extremities. This case report explores the impact of routine CWI on the effectiveness of lipedema reduction surgery (LRS) and manual lipedema extraction, as part of the SMiLE technique (softening, mobilization, liposuction, and extraction). A 59-year-old woman with lipedema presented for LRS of the anterior legs. In the prior 5 months, the patient engaged in daily CWI. During LRS, there was a remarkable amount of lipedema nodules readily extracted compared with a typical patient. The patient’s 5 months of routine CWI resulted in improved quality of life and decreased lipedema symptoms, and may have contributed to the quantity and ease of nodule extraction during LRS.